2011
DOI: 10.1007/s11130-011-0215-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretagogue, Alpha-glucosidase and Antioxidant Activity of Some Selected Spices in Streptozotocin-induced Diabetic Rats

Abstract: Spices are extensively used to enhance the taste and flavor of foods and are known to possess several medicinal properties. Myristica fragrans, Parmelia perlata, Illicium verum, Trachyspermum copticum and Myristica malabarica, the commonly used spices in India were assessed for antidiabetic activity in streptozotocin induced diabetic rats. In the in vitro insulin secretion studies on isolated islets of Langerhans, M. fragrans, T. copticum and M. malabarica showed dose dependent insulin secretion. At 1 mg/ml, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 24 publications
(21 reference statements)
0
31
0
Order By: Relevance
“…Meanwhile, aril was found having higher FRAP and metal-chelating activity than that of seed-kernel. Although there were a few published antioxidant evaluations of the extracts (Chatterjee et al, 2007;Kwon et al, 2008;Patil et al, 2011;Su et al, 2007;Surveswaran et al, 2007;Wojdy1o et al, 2007), the present study apparently is the first comparative report on the different edible parts of M. fragrans. In agreement with the results obtained from this study, the seed extracts of tropical fruits such as jackfruit and mango were also reported having higher antioxidant activities than their edible fleshes (Soong & Barlow, 2004).…”
Section: Antioxidant Activitymentioning
confidence: 80%
See 1 more Smart Citation
“…Meanwhile, aril was found having higher FRAP and metal-chelating activity than that of seed-kernel. Although there were a few published antioxidant evaluations of the extracts (Chatterjee et al, 2007;Kwon et al, 2008;Patil et al, 2011;Su et al, 2007;Surveswaran et al, 2007;Wojdy1o et al, 2007), the present study apparently is the first comparative report on the different edible parts of M. fragrans. In agreement with the results obtained from this study, the seed extracts of tropical fruits such as jackfruit and mango were also reported having higher antioxidant activities than their edible fleshes (Soong & Barlow, 2004).…”
Section: Antioxidant Activitymentioning
confidence: 80%
“…However, no specific evaluation on the antioxidant and antibacterial activities of different parts of M. fragrans has been made. Several comparative antioxidant (Chatterjee et al, 2007;Patil, Ghadyale, Taklikar, Kulkarni, & Arvindekar, 2011;Shan, Cai, Sun, & Corke, 2005;Su et al, 2007;Surveswaran, Cai, Corke, & Sun, 2007;Wojdy1o, Oszmianski, & Czemerys, 2007) and antibacterial assessments (Rani & Khullar, 2004;Mahady et al, 2005;Shekarforoush, Nazer, Firouzi, & Rostami, 2007;Zaidi, Yamada, Kadowaki, Usmanghani, & Sugiyama, 2009) of different spices and medicinal plants had revealed a promising activity of the seed and aril extracts of M. fragrans. The lower minimum inhibitory concentration (MIC) of the extracts against Helicobacter pylori (a gastric bacteria) and Streptococcus mutans (an oral bacteria) revealed their potential values for treating gastrointestinal disorders and as anticariogenic agent (Chung, Choo, Lee, & Hwang, 2006;Mahady et al, 2005;Zaidi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Rats were rendered diabetic by a single intraperitoneal injection of freshly prepared streptozotocin (45 mg/kg body weight) in 0.1 mol/L citrate buffer (pH 4.5) in a volume of 1 mL/kg body weight [3] . Diabetes was identified in rats by moderate polydypsia and marked polyuria.…”
Section: Induction Of Experimental Diabetesmentioning
confidence: 99%
“…100 In addition to C. islandica, the lichen specie Parmelia perlata afforded antidiabetic effect by stimulating insulin secretion. 92 Halici et al 70 demonstrated the potential gastroprotective effect of the aqueous extract of Usnea longissima against indomethacin-induced gastric lesions in rats through an antioxidant mechanism. One year later, this same research team isolated the diffractaic acid and the usnic acid from an organic extract of U. longissima as promising antiulcerogenic agents via inhibition of oxidative damage and neutrophil inltration.…”
Section: Other Activitiesmentioning
confidence: 99%